Antifungal Resistance in Pulmonary Aspergillosis - Verweij, Paul E.; Song, Yinggai; Buil, Jochem B.; Zhang, Jianhua; Melchers, Willem J.G. (Seminars in Respiratory and Critical Care Medicine, 2024)
Aspergilli may cause various pulmonary diseases in humans, including allergic bronchopulmonary aspergillosis (ABPA), chronic pulmonary aspergillosis (CPA), and acute invasive pulmonary aspergillosis (IPA). In addition, chronic colonization may occur in cystic fibrosis (CF). Aspergillus fumigatus represents the main pathogen, which may employ different morphotypes, for example, conidia, hyphal growth, and asexual sporulation, in the various Aspergillus diseases. These morphotypes determine the ease by which A. fumigatus can adapt to stress by antifungal drug exposure, usually resulting in one or more resistance mutations. Key factors that enable the emergence of resistance include genetic variation and selection. The ability to create genetic variation depends on the reproduction mode, including, sexual, parasexual, and asexual, and the population size. These reproduction cycles may take place in the host and/or in the environment, usually when specific conditions are present. Environmental resistance is commonly characterized by tandem repeat (TR)-mediated mutations, while in-host resistance selection results in single-resistance mutations. Reported cases from the literature indicate that environmental resistance mutations are almost exclusively present in patients with IA indicating that the risk for in-host resistance selection is very low. In aspergilloma, single-point mutations are the dominant resistance genotype, while in other chronic Aspergillus diseases, for example, ABPA, CPA, and CF, both TR-mediated and single-resistance mutations are reported. Insights into the pathogenesis of resistance selection in various Aspergillus diseases may help to improve diagnostic and therapeutic strategies.
Keywords: Aspergillus fumigatus; aspergillosis; azole resistance; Cyp51A